Optimization of Nitrogen and Mineral Sources in Liquid Media for Amylase Production Thermophilic Aspergillus sp. LBKURCC304 - Devi, Silvera; Saryono, Saryono; Itnawita, Itnawita; Mukhlis, Mukhlis; Syaifullah, Mhd Muslim (LPPM Universitas Muhammadiyah Riau, 2023)
The application of amylase is relatively large, used in various industries: textiles, pulp and paper, feed, detergents, and food. Therefore, the isolation and optimization of amylase production from various microorganisms has been ongoing. Optimization of amylase production from Aspergillus sp. LBKURCC304 was carried out in liquid media with variable sources of nitrogen (soy flour, tempeh flour or catfish flour) and minerals (FeSO47H2O; CaCl2 2H2O; MgSO4 7H2O; MnSO4 H2O, BaCl2 2H2O) incubated at 50⁰C for 11 days with an agitation speed of 150 rpm. The amylase activity produced was determined by the Nelson-Semogyi method, the protein content by the Lowry method and the specific activity was calculated from the ratio of the amylase activity to the protein content. The research data were statistically tested using ANOVA and the multiple-distance Duncan method at a significance level of 5%. The results of the study showed that the highest amylase activity of 0.0084±0.0014 U/mL was produced in a medium with a nitrogen source of tempeh, the mineral was MgSO4.7H2O, a concentration of 0.05%. The protein content was 0.5111±0.0073 mg/ml and the specific activity was 0.0164±0.00 U/mg.